MRI Findings of Eosinophilic Fasciitis - Michaela Kubincová; Filip M. Vanhoenacker (Journal of the Belgian Society of Radiology, 2022)
Teaching point: Eosinophilic fasciitis (EF) is a rare sclerodermiform disease characterized by upper- and lower-limbs oedema and hardness, which should be confirmed by skin biopsy and MRI in case of clinical suspicion.